Genomic changes of chromosomes 8p23.1 and 1q21: Novel mutations in malignant mesothelioma. (December 2018) - Serio, Gabriella; Vimercati, Luigi; Pennella, Antonio; Gentile, Mattia; Cavone, Domenica; Buonadonna, Antonia Lucia; Scattone, Anna; Fortarezza, Francesco; De Palma, Angela; Marzullo, Andrea
Highlights: Peritoneal malignant mesothelioma is a rare malignancy caused by asbestos exposure. a-CGH was performed to identify genetic imbalances of peritoneal mesothelioma. Loss of function of ubiquitination and defensins and mesothelioma carcinogenesis. Abstract: Introduction: Malignant mesothelioma is an aggressive malignancy of the thoracic cavity caused by prior asbestos exposure. In the peritoneum the mesothelioma is an extremely rare condition. In the present preliminary study, high-resolution array-comparative genomic hybridization (a-CGH) was performed to identify genetic imbalances in a series of malignant peritoneal mesothelioma cases. Materials and methods: Between 1990 and 2008, among the cases recorded in the Apulia Mesothelioma Register, we found 22 peritoneal mesothelioma cases. CGH-array was performed on samples from all patients. Results: The CGH-array analysis revealed multiple chromosomal imbalances. Interestingly, deletion at 8p23.1 was observed in 12 cases. Furthermore, another novel deletion at 1q21 was present in 11. Often, 1q21 and 8p23.1 losses were present in the same patient (7 cases). Losses of BAP1 and CDKN2A loci were not detected. Discussion: The region at 8p23.1 contains the beta-defensin gene cluster (DEF) and 1q21 contains ubiquitin conjugating enzyme E2 (UBE2Q1). We hypotesized that the loss of function of ubiquitination, as well as of the defensins, could play an important role in the initial development and subsequent progression of mesothelioma.